Design of a Virtual Tour as a Solution for Promoting the Tourism Sector in the Pandemic Period - Pahlevi, Andreas Syah; Sayono, Joko; Hermanto, Yon Ade Lose (KnE Social Sciences, 2021)
The COVID-19 pandemic has had a significant impact on the tourism sector. Tourism businesses must adapt to new conditions and rearrange their promotional strategies so that they can survive in the new normal era. Since the pandemic started spreading in early 2020, the Government has recommended a new promotional initiative for the tourism sector through the use of technology that can be accessed remotely via the internet. One of these approaches is the presentation of virtual tourism in various ways to strengthen the brand and promote tourism, for example, through virtual reality. The aim of this research was to increase tourist visits to Kajoetangan Heritage Village through applying technology to create a virtual tourism portal application, thereby raising the attractiveness of thematic village tourist destinations in Malang City. Using the virtual reality design as a form of marketing communication could be an alternative solution to tourism promotion during the pandemic. A Research and Development approach was used in this study in the following order: (1) conducting product analysis to be developed; (2) developing initial products; (3) expert validation and revision; (4) small-scale field trials and product revisions; (5) field trials and final product. The results from the field test showed that users can gain awareness about tourism activities through this virtual reality product, which can therefore be effective in supporting tourism promotion during the pandemic period. Keywords: virtual reality, COVID-19